2019
DOI: 10.1063/1.5082657
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inactivation effects against Escherichia coli O157:H7 biofilm by different plasma-treated solutions and post-treatment storage

Abstract: This study investigated the optimum conditions to maximize the inactivation of biofilms using both plasma-treated solutions and post-treatment storage conditions. Chemical properties of plasma-treated solutions were also analyzed to identify their possible biofilm inactivation mechanisms. Escherichia coli O157:H7 biofilms on stainless steel were prepared and immersed in distilled water (DW), 100 ppm of sodium chloride solution (NaCl), or 100 ppm of sodium hypochlorite solution (NaOCl), followed by container-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…(6 – 7) ( Jo et al, 2020 ). Peroxynitrite is a strong oxidant and bactericidal compound that causes oxidative stress, denaturation of the cell wall, and DNA damage ( An et al, 2019 ). For these reasons, nitrite addition improves the microbial safety of meat products.…”
Section: The Role Of Nitrite In Meat Productsmentioning
confidence: 99%
“…(6 – 7) ( Jo et al, 2020 ). Peroxynitrite is a strong oxidant and bactericidal compound that causes oxidative stress, denaturation of the cell wall, and DNA damage ( An et al, 2019 ). For these reasons, nitrite addition improves the microbial safety of meat products.…”
Section: The Role Of Nitrite In Meat Productsmentioning
confidence: 99%
“…a self-produced biopolymeric matrix that affords microorganism protection, remain elusive. 15,16 Furthermore, these in vitro findings may not necessarily translate to real-life applications where PAW is expected to kill pathogens within a complex, multiorganism system. 17 Indeed, prolonged activation of water can lead to significant localized changes in its pH and concentration gradients of reactive species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, although many studies have shown that PAW possesses unique biochemical reactivity to inhibit a wide range of planktonic microorganisms and even spores, ,, and do so with high selectivity, , most of these studies were conducted in vitro using simple systems, e.g., a suspension of a single species of pathogenic microorganisms. , Relevant mechanisms that underlie the biochemical activity of the agents generated by plasmas in a solution against pathogens within the biofilm, i.e. a self-produced biopolymeric matrix that affords microorganism protection, remain elusive. , Furthermore, these in vitro findings may not necessarily translate to real-life applications where PAW is expected to kill pathogens within a complex, multiorganism system . Indeed, prolonged activation of water can lead to significant localized changes in its pH and concentration gradients of reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several previous studies have shown that PAW has a notable broad-spectrum biocidal activity against bacteria, ,, fungus, and biofilms . The ROS and RNS in PAW, or their synergy, play a crucial role in its biocidal activity, which results in a high oxidation–reduction potential and low pH value.…”
Section: Resultsmentioning
confidence: 99%